Interleukin-10 inhibits chronic angiotensin II-induced pathological autophagy. (December 2015) - Kishore, Raj; Krishnamurthy, Prasanna; Garikipati, Venkata Naga Srikanth; Benedict, Cindy; Nickoloff, Emily; Khan, Mohsin; Johnson, Jennifer; Gumpert, Anna M.; Koch, Walter J.; Verma, Suresh Kumar
Abstract: Background: Although autophagy is an essential cellular salvage process to maintain cellular homeostasis, pathological autophagy can lead to cardiac abnormalities and ultimately heart failure. Therefore, a tight regulation of autophagic process would be important to treat chronic heart failure. Previously, we have shown that IL-10 strongly inhibited pressure overload-induced hypertrophy and heart failure, but role of IL-10 in regulation of pathological autophagy is unknown. Here we tested the hypothesis that IL-10 inhibits angiotensin II-induced pathological autophagy and this process, in part, leads to improve cardiac function. Methods and results: Chronic Ang II strongly induced mortality, cardiac dysfunction in IL-10 Knockout mice. IL-10 deletion exaggerated pathological autophagy in response to Ang II treatment. In isolated cardiac myocytes, IL-10 attenuated Ang II-induced pathological autophagy and activated Akt/mTORC1 signaling. Pharmacological or molecular inhibition of Akt and mTORC1 signaling attenuated IL-10 effects on Ang II-induced pathological autophagy. Furthermore, lysosomal inhibition in autophagic flux experiments further confirmed that IL-10 inhibits pathological autophagy via mTORC1 signaling. Conclusion: Our data demonstrate a novel role of IL-10 in regulation of pathological autophagy; thus can act as a potential therapeutic molecule for treatment of chronic heart disease. Highlights: IL-10 deletion exaggerates pathological myocardial autophagy in response to Ang II. IL-10 treatment attenuates Ang II-induced pathological autophagy. PI3K, Akt or mTORC1 inhibition mitigates IL-10 effect on Ang II-induced autophagy. Lysosome inhibition does not alter autophagic flux in IL-10 treated cells.